Use of flow cytometry for high-throughput cell population estimates in brain tissue - Young, Nicole A.; Flaherty, David K.; Airey, David C.; Aworunse, Feyi; Varlan, Peter A.; Kaas, Jon H.; Collins, Christine E. (Frontiers in Neuroanatomy, 2012)
The numbers and types of cells in an area of cortex define its function. Therefore it is essential to characterize the numbers and distributions of total cells in areas of the cortex, as well as to identify numbers of subclasses of neurons and glial cells. To date, the large size of the primate brain and the lack of innovation in cell counting methods have been a roadblock to obtaining high-resolution maps of cell and neuron density across the cortex in humans and non-human primates. Stereological counting methods and the isotropic fractionator are valuable tools for estimating cell numbers, but are better suited to smaller, well-defined brain structures or to cortex as a whole. In the present study, we have extended our flow-cytometry based counting method, the flow fractionator (Collins et al., 2010a), to include high-throughput total cell population estimates in homogenized cortical samples. We demonstrate that our method produces consistent, accurate and repeatable cell estimates quickly. The estimates we report are in excellent agreement with estimates for the same samples obtained using a Neubauer chamber and a fluorescence microscope. We show that our flow cytometry-based method for total cell estimation in homogenized brain tissue is more efficient and more precise than manual counting methods. The addition of automated nuclei counting to our flow fractionator method allows for a fully automated, rapid characterization of total cells and neuronal and non-neuronal populations in human and non-human primate brains, providing valuable data to further our understanding of the functional organization of normal, aging and diseased brains.